Learning Styles and Instructional Materials as Correlates of Grade 6 Learners`' Mathematics Performance in Buffalo City, South Africa - Kemi Olajumoke Adu; Ntombozuko Duku (Research in Social Sciences and Technology, 2021)
Mathematics is a core subject in South Africa. Studies have shown that the performance of learners on this subject is not encouraging. Many factors have been alluded to by scholars as contributing factors to this poor performance. The gap between theory and practice of mathematics teaching can be bridged by the use of appropriate learning styles, availability, and utilization of instructional. This paper finds out the relationship that exists among learning styles, instructional materials, and mathematics performance of Grade 6. The choice of Grade 6 is important because it is the last grade level of primary school before a learner can enter secondary school level in South Africa. The study adopted a correlational research design of a quantitative approach. Stratified sampling techniques were used to select 1225 learners from Grade 6 schools within Buffalo City Metropolitan Education District. The data revealed among others that in Buffalo City, availability and utilization of instructional materials have no significant relationship with the mathematics performance of selected grade 6 learners (B=.023, t=.804, P≥0.05) while students learning styles (visual, auditory, and kinaesthetic) have a significant relationship with grade 6 learners Mathematics performance (B=-.113, t=-3.886, p<0.05). The study concluded that one of the most fundamental issues to consider in improving Mathematics performance is the understanding of the learners’ learning styles and effective use of appropriate instructional materials for teaching Mathematics.